(untitled) (Bulletin KNOB, 2003)
In the period 1875-1890 the Langstraat railway was constructed in North Brabant. The railway line formed the east-west connection between ’s-Hertogenbosch and Lage Zwaluwe and ran through the Langstraat, traditionally the region where the leather and shoe industry was concentrated. People had high economic expectations for the Langstraat railway, but they did not come true. The 46.5-kilometer-long railway remained a provincial enterprise. Although the intention was to construct a double track, only a single track was realised. As a result it was nicknamed: ‘Halve Zolenlijntje’ (half-sole line). In North Brabant several concrete relics of the Langstraat railway have been preserved. Part of the railway embankment is still in its original state, another part was converted into an intercity bicycle path. In the form of a linear structure in the landscape the Langstraat railway has been preserved in its entirety. Along the railway line there are still some level-crossing keepers’ dwellings (e.g. at Sprang-Capelle and Waalwijk). Besides, various old railway bridges, such as Venkant bridge and Moerputten bridge, have been preserved. The article concentrates on Moerputten bridge, an approximately 585-meter-long sluice in the former inundation area (’de Moerputten’) south-west of ’s-Hertogenbosch. The cultural-historical significance of Moerputten bridge is rich and varied. Apart from its historical importance as a railway bridge on the Langstraat railway line, Moerputten bridge appears to be related to the fortified city of ’s-Hertogenbosch in a hydraulic and military-strategic respect. Moerputten bridge was built as a sluice in order to collect the excess water of the rivers Aa and Maas in winter and spring, and to pass the water through after it had been regulated and let in via Beerse Overlaat. Furthermore, the wetlands of Moerputten were traditionally part of the fortified city of ’s-Hertogenbosch. In times of war the inundation area (’Bossche Inundatieveld’) prevented the enemy’s approach from the south-west, so that Moerputten bridge also had military-strategic significance. But above all, Moerputten bridge is a masterly example of engineering and a striking specimen of 19th-century belief in progress. After part of the Langstraat railway line had been put out of operation in 1972, the railway fell into disrepair. The red lead, finishing coat and the paints that covered Moerputten bridge came off and ended up in the water of Moerputten, which by that time had acquired the status of nature reserve (!). Pollution of soil, sludge and water were the result. The special fauna and flora of the Moerputten nature reserve were at risk. Meanwhile a sound restoration plan is in preparation. The plan was developed by the owner of Moerputten bridge (Dutch Forestry Commission) in co-operation with various interested parties. In the autumn of 2003 a limited trial restoration was started. The further course of the restoration will be largely determined by the results of this trial restoration. As the breeding season will have to be respected, the restoration of Moerputten bridge can only take place between 1 August and 1 March. If things proceed according to plan, the restoration will be completed in 2007. Moerputten bridge will then be given a new use and is to function as a pedestrian bridge.